2007
DOI: 10.1063/1.2713360
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of acoustic streaming in a looped-tube thermoacoustic engine with a jet pump

Abstract: This paper reports on the acoustic streaming in a looped-tube thermoacoustic prime mover equipped with an asymmetric constriction called a jet pump. The time-averaged mass flow velocity was determined using visualization methods and using acoustic field measurements. It was demonstrated that the magnitude and the direction of the velocity were dependent on the orientation of the jet pump. From the observed velocities, we estimated the heat carried away from the hot heat exchanger by the mass flow. It was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…The development of new engine systems using the concept of thermoacoustic instability has recently been attempted by Biwa and coauthors in the field of physics [7][8][9][10]. On the contrary, the complex interaction between the combustion process and the acoustic field inside combustors generates thermoacoustic combustion oscillations with nonlinear dynamic behavior, leading to serious damage in practical combustors such as propulsion and land-based gas-turbine engines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new engine systems using the concept of thermoacoustic instability has recently been attempted by Biwa and coauthors in the field of physics [7][8][9][10]. On the contrary, the complex interaction between the combustion process and the acoustic field inside combustors generates thermoacoustic combustion oscillations with nonlinear dynamic behavior, leading to serious damage in practical combustors such as propulsion and land-based gas-turbine engines.…”
Section: Introductionmentioning
confidence: 99%
“…Self-excited oscillations caused by closed-loop coupling between unsteady heat-release fluctuations, acoustic velocity, and/or the pressure field are an important thermoacoustic instability of much interest in wide a spectrum of combustion, thermal fluid, and physics fields [1][2][3][4][5][6][7][8][9][10]. The development of new engine systems using the concept of thermoacoustic instability has recently been attempted by Biwa and coauthors in the field of physics [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Backhaus and Swift [5] reported that 41% of the Carnot efficiency was achieved in their engine by suppressing the mass flow in the loop. Recently, we have measured quantitatively the mass flow velocity in the looped tube engine [10], and found that more than 30% of the input heat power was carried away by the mass flow. We experienced in the present engine-loop an anomalous heating of the tube in the region (1.21 < x < 1.4 m) between the hot heat exchanger and the connecting position of the loop and the resonator.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19][20][21] The precise measurement of acoustic streaming velocity has also been recently achieved by Thompson et al 22,23 and Moreau et al 24 using laser Doppler velocimetry ͑LDV͒ and appropriate signal processing. Thompson et al measured the Lagrangian outer ͑i.e., outside acoustic boundary layers͒ streaming velocity in a standing wave and they studied the influences of the temperature gradients and the fluid inertia on acoustic streaming.…”
Section: Introductionmentioning
confidence: 97%